Adaptation of institutional arrangements to management of Northern Rangelands of Kenya - Kanyuuru, C.K.; Mburu, J.; Njoka, J. (Springer, 2017)
Northern Rangelands of Kenya have continued to grapple with management challenges largely due to a lack of understanding of the dynamics thereof. Eroding customary institutions and new institutional arrangements characterize the system suggesting that adaptation is taking place to cope with the change. It is imperative that these socio-ecosystems adjust to the disturbance without disintegrating into a different state that is controlled by a different set of processes to ensure sustainable rangeland management. To understand the nature of change, the study sought to evaluate institutional arrangements engaged in tackling growing socio-economic and ecological factors challenging development within the last decade. Three study sites namely Kinna, Makurian and Westgate, representing three types of institutional arrangements (elders only, group ranch committee and community conservancy board), were investigated. Key informants, focused group discussions and household survey methods were used to gather data. Data were managed and analysed using Ms Access, Ms Excel, social network analysis and SPSS. Findings indicate that more actors (internal and external) are engaging in management of social economic and ecological factors challenging development within the last decade. The co-management approach allows increased capacity to tackle these challenges and further presents more opportunities for a diversified livelihood, two key features of ecosystem resilience. Findings are useful as the Kenya government implements the National Land Policy that recognizes the need to restructure community land and its management.